Ambientes colaborativos virtuales para el aprendizaje individual - González Herrera, Denis (Universidad de Costa Rica, 2017)
Abstract: This article presents the research results about virtual collaborative environments, in which a group of 15 students from the University of Costa Rica participated. The objective of the research was to innovate in the formulation of methodological and pedagogical techniques that help to involve the student-instructor, as actors in the training processes. This was achieved through the empowerment of information and communication technologies (ICT) and especially using mobile devices. The research was carried out in 2014, from a mixed approach that systematizes the process, experiences and lessons learned. The data were obtained by a self-administered instrument, supplied in a single moment; moreover, the observations of the participants were recorded during the whole cycle. The research helped to identify technological tools that allow innovating in the creation of collaborative environments; in addition, it was demonstrated that these increase and improve the experience of the learning process. It also demonstrates that the collaborative environments can be created with free and accessible software tools; and that minimal computer skills are required to customize it according to educational needs. Finally, a proposal is presented for a five-stage model that allows other teachers to replicate this type of environment; which was a guide in the creation of a fully functional mobile application that can be studied in future research.